Islam in a zongo: Muslim lifeworlds in Asante, Ghana - Pontzen, Benedikt ca. 20./21. Jh. (The international African library, 2021)
Zongos, wards in West Africa populated by traders and migrants from the northern savannahs and the Sahel, are a common sight in Ghana's Asante region where the people of these wards represent a dual-minority as both foreigners and Muslims in a largely Christian area, facing marginalisation as a result. Islam provides the people of the zongos with a common ground and shared values, becoming central to their identity and to their shared sense of community. This detailed account of Islamic lifeworlds highlights the irreducible diversity and complexity of 'everyday' lived religion among Muslims in a zongo community. Benedikt Pontzen traces the history of Muslim presence in the region and analyses three Islamic phenomena encountered in its zongos in detail: Islamic prayer practices, the authorisation of Islamic knowledge, and ardently contested divination and healing practices. Drawing on empirical and archival research, oral histories, and academic studies, he demonstrates how Islam is inextricably bound up with the diverse ways in which Muslims live it.